2008
DOI: 10.1111/j.1365-2427.2008.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of plant strategies in fluvial hydrosystems

Abstract: SUMMARY1. We propose a model of plant strategies in temperate fluvial hydrosystems that considers the hydraulic and geomorphic features that control plant recruitment, establishment and growth in river floodplains. 2. The model describes first how the disturbance gradient and the grain-size of the river bed load affect the relative proportion of erosion and deposition processes, and how the frequency of flood disturbance affects the intensity of such processes. 3. Secondly, the model predicts plant strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 140 publications
(154 reference statements)
7
159
1
4
Order By: Relevance
“…Some wetlands are isolated except during the river's flood pulse (sensu Junk et al 1989), whereas others remain continually connected through breaks in the river channel's levees (Filgueira-Rivera et al 2007). This creates a gradient in connectivity to the river and water residence time (Hermoso et al 2012), which we predict will correspond with the degree to which the river's flood pulse influences wetland vegetation (Bornette et al 2008) and the spatial distribution of flood response guilds.…”
Section: Introductionmentioning
confidence: 93%
“…Some wetlands are isolated except during the river's flood pulse (sensu Junk et al 1989), whereas others remain continually connected through breaks in the river channel's levees (Filgueira-Rivera et al 2007). This creates a gradient in connectivity to the river and water residence time (Hermoso et al 2012), which we predict will correspond with the degree to which the river's flood pulse influences wetland vegetation (Bornette et al 2008) and the spatial distribution of flood response guilds.…”
Section: Introductionmentioning
confidence: 93%
“…As the literature on physical conditions in springs is relatively scarce, some terms, concepts and observations provided by such environments can partly be applied to spring ecosystems. Bornette et al (2008) hypothesized that species able to survive in high-flow conditions harbor specific phenotypes and/or reproduction ways and provide examples of the effect of physical conditions on biocenoses patterns. Thus, the plant size, form and stand structure, together with the strength of its stems and method of anchoring, constrains its presence to a specific physical environment.…”
Section: Spring Ecosystemsmentioning
confidence: 99%
“…The extent of alluvial plains increases. The periodicity of floods (controlling aggradation and degradation processes), the nature of the alluvium (which depends on erosion process at the catchment scale), the occurrence and form of meanders, dams and cut-off channels, and the groundwater depth, constrain the repartition of vegetation (Vannote et al 1980;Pinay et al 1990;Ward et al 2002;Bornette et al 2008). Therefore, characterization and conceptualization of terrestrial GDEs should take into account longitudinal, lateral (related to particle-size distribution and geochemistry of the terraces and flood frequency) and vertical dimensions (related to granulometry profile and groundwater level fluctuations) of the fluvial hydrosystem (Amoros and Petts 1993;Ward 1998;Lyon and Gross 2005;Derx et al 2010).…”
Section: Peatland Gdesmentioning
confidence: 99%
“…Nevertheless, many authors regard river-driven disturbance as the main component controlling riparian vegetation processes (e.g., Poff et al 1997;Nilsson and Svedmark 2002;Camporeale and Ridolfi 2006;Corenblit et al 2007). In particular, flow and flood regimes control riparian vegetation colonisation and development (Bornette et al 2008). Ye et al (2013) built a model to predict which hydrological component is dominant in affecting vegetation cover in riparian zones, and they concluded that floods are the main regulating process.…”
Section: Introductionmentioning
confidence: 99%